2016
DOI: 10.4236/jamp.2016.411198
|View full text |Cite
|
Sign up to set email alerts
|

Observing the Jumping Laser Dogs

Abstract: Jumping sun dogs are rapid light flashes changing over clouds, with some of them located close to the places of halo formation in thunder storms clouds. This paper presents an outline of some aspects that are required for understanding the jumping sun dogs, using some experiments with light scattering in complex fluids. In our analogy, we have observed the jumping laser dogs, in which the ice crystals are replaced by needlelike structures of ferrofluid, the electric field in the atmosphere is represented by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Later, in [4] a hypothesis explaining an atmospheric optical phenomenon commonly called the miracle of the sun as a result of the passing of sunlight through a synchronously vibrating electrically charged cloud of ice crystals was presented. This hypothesis was then extended to other similar phenomena by other authors [5]. In the following years, the theoretical model of vibrations of synchronous clouds of electrically charged ice crystals was extended.…”
Section: Analysis Of the Problemmentioning
confidence: 74%
“…Later, in [4] a hypothesis explaining an atmospheric optical phenomenon commonly called the miracle of the sun as a result of the passing of sunlight through a synchronously vibrating electrically charged cloud of ice crystals was presented. This hypothesis was then extended to other similar phenomena by other authors [5]. In the following years, the theoretical model of vibrations of synchronous clouds of electrically charged ice crystals was extended.…”
Section: Analysis Of the Problemmentioning
confidence: 74%
“…In this way, the image obtained from the Ferrolens in Figure 2a is related to the magnetic field obtained with the gaussmeter of Figure 4b, and the light pattern of Figure 2b is associated with the magnetic field of Figure 4d. One way to see directly what is happening inside the Ferrolens is by obtaining the polarimetry of the Ferrolens, see References [2][3][4]10] for more detailed discussions about the light polarization effects of this device. We observed that the nanoparticles create a diffracting grating following the orientation of the magnetic field, forming a needle-like structure locally.…”
Section: Condens Matter 2019 4 X For Peer Reviewmentioning
confidence: 99%
“…The observed pattern suggests a resemblance of the polarimetry of Ferrolens with the concept of spatial mode of Equation 3and other hypergeometric polynomials empirically. We have approximated the intensity of light polarization I observed for magnetic field B [2,10] as…”
Section: Condens Matter 2019 4 X For Peer Reviewmentioning
confidence: 99%
See 2 more Smart Citations